The Effect of Use of Local Organic Microorganism Fertilizers on Rice Media, Banana Sticks, And Tongol Fish on The Growth of Arabika Coffee Plants (Coffea arabica L.) in The Gunung Karang Garden, Pandeglang District - Suyamto, Suyamto; Hujaji, M.; Susilo, Hadi; Oktavia, Swastika; Mu'jijah, Mu'jijah (Biology, Medicine, & Natural Product Chemistry, 2024)
Arabica coffee plants (Coffea arabica L.) are plantation commodities with high economic value. Efforts that can be made in farming without using chemicals that will damage the environment is by utilizing local microorganisms (MOL). For farmers who demand the use of cheap and practical fertilizers, they can be directed to use local microorganism organic fertilizers made from rice, banana stems, and tuna. This study aims to determine the effect of using local microorganism organic fertilizers made from rice, banana stems, and tuna on the growth of C. arabica plants. The type of research to be carried out is experimental research. This research method uses a Completely Randomized Factorial Design (CRFD) consisting of 2 factors and 3 replications. The first factor is the source material consisting of 3 levels, namely: M1 = stale rice, M2 = banana stem, and M3 = tuna. The second factor is the fermentation period consisting of: H1 = 2 weeks fermentation and H2 = 4 weeks fermentation. The measured parameters of C. arabica plants are height, number of leaves, and stem diameter. The results showed that rice, banana stem, and tuna can be made into MOL fertilizers. The use of MOL organic fertilizers (stale rice, banana stem, and tuna) affects the growth of C. arabica, which can be seen from the parameters of plant height, number of leaves, and stem diameter. M3H2 MOL organic fertilizer (tuna fermented for 4 weeks) provides optimal growth of C. arabica in terms of plant height, number of leaves, and stem diameter.